FANATISME BONEK PADA AKUN X @GREEN_NORD27 - Muhammad Rizqi Himawan; Kusuma, Ade (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
The X application facilitates the formation of virtual communities centered around shared interests, including various fan bases. Many enthusiasts of sports, music, politics, and other fields utilize X as a platform to connect and engage in discussions. Persebaya Surabaya, as the largest football supporter community in Indonesia, has an X account with the username @green_nord27. In Indonesia, football transcends being merely a sport; it has evolved into a cultural phenomenon characterized by the intense passion of its supporters. This study explores the expression of fanaticism among Bonek, the supporters of the Persebaya Surabaya club, on the X social media platform @green_nord27. The account is managed by the Green Nord 27 community, one of the largest fan bases of Persebaya. The primary aim of this study is to analyze how supporters express their fanaticism in the digital realm and to identify the factors contributing to this phenomenon. This research adopts a qualitative descriptive approach and utilizes various data collection methods, including literature review, documentation, observation, and in-depth interviews. The findings reveal that fanatical supporters demonstrate their passion not only through their physical presence in stadiums but also through active participation in digital activities and the creation of collective identities via digital symbols. This form of digital fanaticism fosters group solidarity and a strong sense of belonging within the community.